2012
DOI: 10.2527/jas.53943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of formic acid and phytase supplementation on digestibility and use of phosphorus and zinc in growing pigs

Abstract: Two studies, arranged according to a 4 × 4 Latin square design, were conducted to assess effects of dietary acidification on fungal 3-phytase (PHY) efficacy in growing pigs. In Exp. 1, effects of supplementing 500 units/kg feed of PHY and 4.7 g/kg HCOOH either alone or in combination on the use of P and Zn in growing pigs fed a pelleted diet based on wheat (Triticum aestivum), barley (Hordeum vulgare), and soybean (Glycine max) meal were investigated. In Exp. 2 the same dietary treatments were fed except that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…However, published information on the effects of organic acids introduced in pig or chicken diets, with or without phytase, is inconclusive. Either organic acids do not improve (Brenes et al, 2003;Bikker et al, 2011;Blank et al, 2012;Swiatkiewicz and Arczewska-Wlosek, 2012) or improve only slightly Pallauf, 1993, 1994;Roth et al, 1998) zinc availability.…”
Section: Use Of Organic Acidsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, published information on the effects of organic acids introduced in pig or chicken diets, with or without phytase, is inconclusive. Either organic acids do not improve (Brenes et al, 2003;Bikker et al, 2011;Blank et al, 2012;Swiatkiewicz and Arczewska-Wlosek, 2012) or improve only slightly Pallauf, 1993, 1994;Roth et al, 1998) zinc availability.…”
Section: Use Of Organic Acidsmentioning
confidence: 98%
“…There is evidence of improved zinc availability by the use of microbial phytase in broilers (e.g. Thiel et al, 1993;Biehl et al, 1995;Yi et al, 1996;Mohanna and Nys, 1999b;Jondreville et al, 2007), in pigs (Pallauf et al, 1992(Pallauf et al, , 1994Lei et al, 1993;Adeola et al, 1995;Revy et al, 2004Revy et al, , 2006Jondreville et al, 2005;Bikker et al, 2012a, b;Blank et al, 2012) and in fish (Cheng and Hardy, 2003;Laining et al, 2012). These experiments indicate that improvements in zinc availability are far lower in broilers than in pigs, with an equivalency of 5 mg zinc in broilers and 27−30 mg zinc from sulphate in piglets at 500 FTU as 3-phytase from Aspergillus niger (Jondreville et al, 2005(Jondreville et al, , 2007Revy et al, 2006).…”
Section: Use Of Exogenous Microbial Phytasementioning
confidence: 99%
See 1 more Smart Citation
“…Tsiloyiannis et al showed a positive effect on controlling post-weaning diarrhea [ 22 ]. Blank et al showed that supplementation of formic acid along with microbial phytase could increase the efficacy of the phytase [ 72 ]. The application of formic acid with essential oils or other organic acids was reported to increase the apparent fecal digestibility of crude fiber in weaning pigs, and the combination with essential oils also appeared to improve non-starch polysaccharide (NSP) and total carbohydrate digestibility [ 73 ].…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Effects of dietary Zn source included in corn–SBM-based diets differing in Zn, phytate, and exogenous phytase (500 FYT Aspergillus niger phytase/kg feed) content were assessed in piglets [ 160 ]. Phytase supplementation increased soluble Zn in the stomach and tended to increase soluble Zn content in the intestine, possibly by lowering gastric pH and resulting in increased mineral solubility [ 145 , 161 ].…”
Section: Utilization Of Selected Minerals In Pigsmentioning
confidence: 99%